The Remineralization of Enamel from Saliva: A Chemical Perspective - Joachim Enax; Pascal Fandrich; Erik Schulze zur Wiesche; Matthias Epple (Dentistry Journal)
The natural remineralization of enamel is of major importance for oral health. In principle, early erosions (demineralization) induced by acidic beverages and foods as well as initial caries lesions can be covered and remineralized by the deposition of calcium phosphate, i.e., tooth mineral. This remineralization effect is characterized by the presence of calcium and phosphate ions in saliva that form hydroxyapatite on the enamel surface. Although it is apparently a simple crystallization, it turns out that remineralization under in vivo conditions is actually a very complex process. Calcium phosphate can form a number of solid phases of which hydroxyapatite is only one. Precipitation involves the formation of metastable phases like amorphous calcium phosphate that convert into biological apatite in a number of steps. Nanoscopic clusters of calcium phosphate that can attach on the enamel surface are also present in saliva. Thus, remineralization under strictly controlled in vitro conditions (e.g., pH, ion concentrations, no additives) is already complex, but it becomes even more complicated under the actual conditions in the oral cavity. Here, biomolecules are present in saliva, which interact with the forming calcium phosphate mineral. For instance, there are salivary proteins which have the function of inhibiting crystallization to avoid overshooting remineralization. Finally, the presence of bacteria and an extracellular matrix in plaque and the presence of proteins in the pellicle have strong influences on the precipitation on the enamel surface. The current knowledge on the remineralization of the enamel is reviewed from a chemical perspective with a special focus on the underlying crystallization phenomena and the effects of biological compounds that are present in saliva, pellicle, and plaque. Basically, the remineralization of enamel follows the same principles as calculus formation. Notably, both processes are far too complex to be understood on a microscopic basis under in vivo conditions, given the complicated process of mineral formation in the presence of a plethora of foreign ions and biomolecules.